Plasmid-mediated ROB-1 beta-lactamase in Pasteurella multocida from a human specimen. - Rosenau, A (1991)
A Pasteurella multocida human isolate was resistant to beta-lactams because of production of ROB-1 beta-lactamase. The beta-lactamase was encoded by a 4.3-kb plasmid closely related to that of a Pasteurella bovine strain, as shown by Sau3A restriction profile and hybridization with a plasmid probe containing the blaROB-1 gene.